(untitled) (Global Journal of Human-Social Science, 2023)
Background Video gaming has become an increasingly popular and globally recognized phenomenon in recent years While playing there are multi repetitive movements of the fingers which may lead to significant hand grip or pinch grip problems Purposes The purpose of this study was to investigate the effect of prolonged use of video games on the grip and pinch strength Materials and Methods Forty male students from King Abdulaziz University participated in this study their age ranged from 18-24 years They were divided into two groups prolonged user and non- user group The hand grip and pinch strength for all participants were measured by a handheld dynamometer and the level of video game addiction was assessed by Game Addiction Test Results There was a significant decrease in hand grip strength of the prolonged user group compared with non-user group while there was a non-significant difference between both groups in the pinch strength The result showed a nonsignificant correlation between hours of playing and Video game addiction Teat VAT with hand grip strength and pinch strength Conclusion There was a significant decrease in hand grip strength of the prolonged users of video games while there was a non-significant decrease in the pinch strength in the prolonged user group compared with non- user group